Rekonstruksi Masa Jabatan Keuchik di Aceh Pasca Putusan Mahkamah Konstitusi Nomor 40/PUU-XXIII/2025 - Agung Munandar; Muhammad Nahyan Zulfikar; Muharrir Muharrir; Putri Kemala Sari (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2026)
The regulation of the term of office of keuchik (village head) in Aceh reflects a normative conflict between Law Number 11 of 2006 concerning the Governing of Aceh (UUPA) and Law Number 6 of 2014 concerning Villages as amended by Law Number 3 of 2024. UUPA stipulates a six-year term of office, while the Village Law provides an eight-year term for village heads. This difference creates legal dualism and raises issues of legal certainty, particularly after the Constitutional Court Decision Number 40/PUU-XXIII/2025, which upheld the validity of the UUPA provisions. This study aims to analyze the position of UUPA within the hierarchy of laws and regulations, examine the application of the principle of lex specialis derogat legi generali, and assess the juridical implications of the Constitutional Court’s decision. This research employs a normative juridical method using statute, conceptual, and case approaches. The findings reveal that the application of lex specialis in this context is partial and inconsistent, as the specific regulation is only maintained in relation to the term of office, while other aspects of village governance, including governance mechanisms at the gampong (village) level, follow national legal frameworks. This inconsistency leads to disharmony within the legal system. Therefore, the reconstruction of the term of office of keuchik becomes necessary by aligning it to eight years, accompanied by strengthened oversight mechanisms to ensure accountability and prevent abuse of power.